An Optimization Study of an Intermittent-Flow Multistage Fluidized Ion Exchange Column with Fluid Diode Downcomers - Egan, Stephen Martin (My University, 1971)
An optimization study of an intermittent-flow multistage fluidized ion exchange column was performed using a stochastic approximation method. A new type of downcomer, a fluid diode, was designed and employed to alleviate liquid bypassing through the downcomer. The well known ion exchange system, H⁺/Na⁺ exchange on Dowex 50W resin, was used in this work.
The volumetric efficiency of the system was optimized with regard to certain column and diode parameters. A maximum volumetric efficiency of 71.8 hr⁻¹ was obtained for the following conditions:
average liquid flowrate = 3661 ml/min ;
resin flowrate = 56.1 gm/min ;
plate spacing 11.43 cm ;
lateral diode displacement= 0.794 cm.
Experiments have shown that a 78.2% increase in volumetric efficiency was achieved by use of the fluidic diode downcomers.
Keywords: chemical engineering; optimization study; intermittent-flow multistage fluidized; ion exchange column; fluid diode, downcomer